2008
DOI: 10.1039/b801620h
|View full text |Cite
|
Sign up to set email alerts
|

Large oriented mesoporous self-supporting Ni–Al oxide films derived from layered double hydroxide precursors

Abstract: Large (~1 cm 2 ) transparent highly (111)-oriented mesoporous self-supporting Ni-Al oxide films of uniform small nanoparticles have been prepared using an Ni 2 Al(OH) 6 (NO 3 )$2.1H 2 O layered double hydroxide (LDH) as a single precursor. The monodisperse small LDH nanoparticles (about 20 nm in diameter) are first cast as an oriented assembly on a glass substrate to form large transparent self-supporting (00l)-oriented LDH films. Subsequent heating in air affords (111)-oriented mesoporous Ni-Al oxide films pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…We suggest that this can account for the marked difference in the magnetic stabilities (as shown by the T B values) of the NiFe 2 O 4 /NiO nanocomposites synthesized from the LDH precursor and by the chemical coprecipitation method. In the case of the LDH, during the early stages of the transformation, oxide nucleation occurs on its (00l) planes where the packing of cations is the densest, giving the lowest nucleation energy, and resulting in the formation of the (111) [20] of the decomposition of the LDH accounts for the close structural dependence of the resulting NiFe 2 O 4 and the NiO matrix and the much better quality of the interface between the NiO matrix and the NiFe 2 O 4 nanoparticles. Moreover, it can be seen from the TEM results that the sizes of the nanoparticles derived from the LDH precursor are much smaller than those obtained from the precursor prepared by the coprecipitation method and are strongly clustered with each other, giving a larger effective AFM NiO phase "thickness" around the NiFe 2 O 4 nanoparticles.…”
Section: Blocking Temperature Of Nife 2 O 4 /Nio Nanocomposites and Mmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that this can account for the marked difference in the magnetic stabilities (as shown by the T B values) of the NiFe 2 O 4 /NiO nanocomposites synthesized from the LDH precursor and by the chemical coprecipitation method. In the case of the LDH, during the early stages of the transformation, oxide nucleation occurs on its (00l) planes where the packing of cations is the densest, giving the lowest nucleation energy, and resulting in the formation of the (111) [20] of the decomposition of the LDH accounts for the close structural dependence of the resulting NiFe 2 O 4 and the NiO matrix and the much better quality of the interface between the NiO matrix and the NiFe 2 O 4 nanoparticles. Moreover, it can be seen from the TEM results that the sizes of the nanoparticles derived from the LDH precursor are much smaller than those obtained from the precursor prepared by the coprecipitation method and are strongly clustered with each other, giving a larger effective AFM NiO phase "thickness" around the NiFe 2 O 4 nanoparticles.…”
Section: Blocking Temperature Of Nife 2 O 4 /Nio Nanocomposites and Mmentioning
confidence: 99%
“…level [19], and the mechanism of the transformation from the LDH precursor to the final composites has been investigated in detail [20][21][22]. The structure of the LDH precursor belongs to the hexagonal group, and the cations on the (00l) facets are arranged in an ordered "hexagon" formation.…”
Section: Introductionmentioning
confidence: 99%
“…[21]. The increase in d-spacing as the Ca/Fe ratio increased can be attributed to the decreased electrostatic interaction between the positively charged layers and the negatively charged interlayer anions [22].…”
Section: Characterization Of the Fresh Catalystsmentioning
confidence: 95%
“…For example, alkoxideintercalated LDHs have been synthesized in a nonaqueous media (methanol), and the hydrolysis of these LDH derivatives resulted in a colloidal LDH suspension which can be used as a precursor for the formation of continuous transparent films via solvent evaporation [18,19]. For another example, the fabrication of oriented LDHs films without organic solvents has been attempted, and separate nucleation and aging steps (SNAS) were adopted as a main method [20]. Due to the uniform and small crystal size (about 40 nm) of the LDH platelets, both the face-to-face and edge-to-edge interactions occur between individual LDH platelets, which facilitate the formation of densely packed c-oriented LDH film [21].…”
Section: Optical Properties Of Ldhsmentioning
confidence: 99%
“…This composite UTF was illustrated as (BTBS/LDH) 12 (QD-530/ LDH) 20 (QD-620/LDH) 7 , composed of three chromophores: red-emission and green-emission QDs and blue-emission organic compound BTBS. Due to the different excitation and emission spectra of these three chromophores, it can be concluded that BTBS can be excited at 360 nm while photon energy above 500 and 600 nm can efficiently excite QD-530 and QD-620.…”
Section: Construction Of Tunable Multicolor Emissive Film Materialsmentioning
confidence: 99%